Is 'tagging' a rationale for affirmative action in education? - Sollaci, Alexandre Balduino (2014)
In this paper, we try to rationalize the existence of one of the most common affirmative action policies: educational quotas. We model a two period economy with asymmetric information and endogenous human capital formation. Individuals may be from two different groups in the population, where each group is defined by an observable and exogenous characteristic. The distribution of skills differ across groups. We introduce educational quotas into the model by letting the planner reduce the effort cost that a student from one of the groups has to endure in order to be accepted into a university. Affirmative action policies can be interpreted as a form of ``tagging' since group characteristics are used as proxies for productivity. We find that although educational quotas are usually efficient, they need not subsidize the education of the low skill group.